A muscle-centric view of time-restricted feeding for older adults. Issue 6 (November 2021) - Lees, Matthew J.; Hodson, Nathan; Moore, Daniel R.
Abstract : Purpose of review: The practice of time-restricted feeding (TRF) has received fervent interest in recent years as a strategy to mitigate obesity and metabolic disease. We sought to review the implications of TRF for skeletal muscle health and function in aging. Recent findings: TRF has high adherence and can promote body weight loss in older populations. Body weight reductions favor fat mass in the young, however, there is also the potential for undesirable losses in lean mass. There is currently no evidence to support TRF for skeletal muscle function and metabolism in older persons, and only tentative findings in the young. With a narrow eating window of 6–8 h and a prolonged fasting period to minimize daily insulin exposure, TRF may contradict recommended dietary practices for optimizing skeletal muscle anabolism in older people. Summary: TRF might represent a promising intervention to address obesity and its associated metabolic diseases, however, at present there is insufficient evidence for optimizing skeletal muscle mass or health in older individuals. Further research is needed to: (1) ascertain the impact of TRF on body composition, skeletal muscle anabolism, and autophagy in aging, and; (2) delineate the potentially myoprotective roles of dietary protein and exercise within the framework of TRF in older persons.